Correction of Medial Blowout Fractures According to the Fracture Types. Issue 1 (January 2016) - Chung, Kyu Jin; Lim, Jong Hyo; Kim, Tae Gon; Lee, Jun Ho; Kim, Yong-Ha
Abstract : Background: Regarding the issue of blowout fracture, a variety of approaches and surgical techniques have been reported to improve postoperative results. However, there are no extant guidelines for the selection of these various methods. The current authors classified the medial blowout fracture into 3 different types and adapted to suitable surgical techniques. Methods: Between October 2010 and March 2013, 89 patients who had medial blowout fracture were included in this study. We classified the study patients into 3 different categories: greenstick, simple, and complex. The greenstick type used the transnasal endoscopic approach and was reduced with packing after applying a silastic sheet. The simple type used an onlay covering technique. The complex type was treated using the transcaruncular approach and inlay implanting technique. After surgery, the continuity of orbital wall was checked by computed tomography. Patients were then examined for the following conditions: diplopia, eyeball movement, and enophthalmos. Results: The greenstick category consisted of 12 cases, most cases were satisfied. One case relapsed after removal of the packing. In the simple category, a total of 9 cases were treated by onlay covering technique. In all 68 cases of the complex type, we could obtain suitable anatomical reconstruction with inlay implanting technique. Only 2 cases complained of transient diplopia and moderate enophthalmos. Conclusions: Appropriate clinical classification, depending on the type of fracture and selection of optimal treatment methods, could obtain the satisfactory result and improve the treatment outcomes in the correction of medial orbital wall fracture.